Clinician tasking in ambulance control improves the identification of major trauma patients and pre-hospital critical care team tasking. Issue 5 (May 2018) - Sinclair, Neil; Swinton, Paul A.; Donald, Michael; Curatolo, Lisa; Lindle, Peter; Jones, Steph; Corfield, Alasdair R.
Abstract: Introduction: Trauma remains the fourth leading cause of death in western countries and is the leading cause of death in the first four decades of life. NICE guidance in 2016 advocated the attendance of pre-hospital critical care trauma team (PHCCT) in the pre-hospital stage of the care of patients with major trauma. Previous publications support dispatch by clinicians who are also actively involved in the delivery of the PHCCT service; however there is a lack of objective outcome measures across the current reviewed evidence base. In this study, we aimed to assess the accuracy of PHCCT clinician led dispatch, when measured by Injury Severity Score (ISS). Methods: A retrospective cohort study over a 2 year period pre and post implementation of a PHCCT clinician led dispatch of PHCCT for potential major trauma patients, using national ambulance data combined with national trauma registry data. Results: A total of 99, 702 trauma related calls were made to SAS including 495 major trauma patients with an ISS >15, and a total of 454 dispatches of a PHCCT. Following the introduction of a PHCCT clinician staffed trauma desk, the sensitivity for major trauma was increased from 11.3% to 25.9%. The difference in sensitivity between the pre and post trauma desk group was significant at 14.6% (95% CI 7.4%–21.4%, p < .001). Discussion: The results from the study support the results from other studies recommending that a PHCCT clinician should be located in ambulance control to identify major trauma patients as early as possible and co-ordinate the response.